Queering borders: Language, sexuality and migration - Murray, David A.B. (Journal of Language and Sexuality, 2014)
Preface to the special issue on queering borders in the journal of language and sexuality.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; canada; cours; discipline; histoire et politique; identités LGBTQIA2+; migration; migrations queer; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques